PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI POSYANDU CEMPAKA IV DESA MEKAR JAYA METODE WATERFALL - Fery Purnama; Dika Pratama; Tamrin Syah (FORTECH (Journal of Information Technology), 2025)
Posyandu Cempaka IV in Mekar Jaya Village still uses manual recording with books and Microsoft Excel in processing health data for mothers, toddlers, and the elderly. This often causes delays in data collection, writing errors, difficulties in data searching, and incomplete reports. Therefore, it is necessary to design a web-based information system that can assist posyandu cadres in managing data in a more structured and efficient manner. This study uses the Waterfall method with UML (Unified Modeling Language) as a modeling tool, and is developed using Visual Studio Code, PHP, MySQL, and XAMPP. The result of this research is a web-based information system that facilitates cadres in data collection and report generation, as well as providing convenience for the community in accessing information about posyandu services.